Introduced fish displace the white-throated dipper (Cinclus cinclus) from high-mountain lakes - Lucia Bello; Teresa Buchaca; Anna Corapi; Nerina Gilbert; Milo Manica; Giorgia Mattioli; Michelangelo Morganti; Víctor Osorio; Quim Pou-Rovira; Ibor Sabás; Cassandra Tassi; Marc Ventura; et al. (Biodiversity and Conservation, 2026)
The introduction of fish into originally fishless high-mountain lakes can strongly alter aquatic food webs. Littoral aquatic macroinvertebrates are heavily preyed upon by fish, yet they also represent an important food resource for several terrestrial and semi-aquatic insectivorous species, including the unique diving passerine, the white-throated dipper ( Cinclus cinclus ). We tested whether competition for this shared resource reduces dipper occurrence, consistent with the competitive exclusion hypothesis. More than 400 visual surveys were conducted to detect dippers across 60 high-mountain lakes in the Alps and Pyrenees. Lakes were categorized as fish-free, undergoing mechanical fish eradication, or hosting established fish populations. Large benthic macroinvertebrates (i.e., the primary prey of dippers) were also assessed to evaluate the likelihood of dipper occurrence across lake categories and along a prey availability gradient influenced by fish predation, as well as other environmental factors (e.g., elevation, hydrological connectivity). Introduced fish negatively affected dipper occurrence, with lakes largely avoided when fish were present, while hydrological connectivity with streams emerged as a key factor facilitating dipper use of high-mountain lakes. This pattern appears to be driven by competitive exclusion via the depletion of large benthic macroinvertebrates. Even though dippers can thrive in areas without high-mountain lakes, relying exclusively on riverine habitats, their association with pristine fishless lakes, together with their recognizability and public appeal, make them effective flagship species to stimulate broader discussion on the impacts of invasive species in mountain freshwater ecosystems and their consequences for native fauna.